KINERJA GURU TERSERTIFIKASI PADA MATA PELAJARAN EKONOMI - Lina Rifda Naufalin (Jurnal Pendidikan Insan Mandiri, 2012)
The study aims to describe (1) performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java indicated from pedagogic competence (2) performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java indicated from professional competence (3) performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java indicated from social competence (4) performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java indicated from personal competence (5) the phenomenon underlying performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java.This research was carried out in the Senior High School in the Distric of Jepara. Qualitative Descriptive is used as research method. The population in this research were all certified teachers on economic subjects in the Jepara Senior High Schools. Purposive sampling is used as sampling techniques. The sample of the research comprised a total of 11 teachers consist of 3 certified economic teachers in the Senior High School ofWelahan, 3 certified economic teachers in the Senior High School of Pecangaan, 2 certified economic teachers in the Senior High School of Jepara, 3 certified economic teachers in the Senior High School of PGRI. The techniques of data collection were interviews, observation and documentation. The techniques of data analysis used interactive analysis.Result and conclusions of this study is the performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java has not been fully showed the change, because (1) indicated from pedagogical competence, teacher set learning goals just based on the syllaby, regardless of the needs and the conditions of the students, besides that the eight of teaching skills can not be done well. (2) indicated from personal competence, teachers have played the main role as models for their students in order the students had promises to improve their discipline and responsibilities for themselves. (3) indicated from professional competence, speech method is often used as teaching method, so there are still many learning resources are unused by teachers, such as libraries, school cooperatives, markets and the willingness of the teachers to improve their professionalism by training, workshops, seminars and lectures are still low. (4) indicated from social competence teachers have responsibility for their profession as intelligent person who is demanded to be able contribute their ideas for the surrounding communities (5) the phenomenon underlying the performance of certified teachers on economic subjects in the Senior High School, in Jepara Distric, Central Java of which teachers do not have good management in teaching-learning, teachers do not have a genuine intention to teach, and the facilities provided by the school do not support the current method, there are socio-cultural factors that affect the appearance of the teachers in the society.Key words: Performance of Teacher, Teacher's Certified